2007
DOI: 10.1146/annurev.nutr.27.061406.093621
|View full text |Cite
|
Sign up to set email alerts
|

Creatine: Endogenous Metabolite, Dietary, and Therapeutic Supplement

Abstract: Creatine and phosphocreatine serve not only as an intracellular buffer for adenosine triphosphate, but also as an energy shuttle for the movement of high-energy phosphates from mitochondrial sites of production to cytoplasmic sites of utilization. The spontaneous loss of creatine and of phosphocreatine to creatinine requires that creatine be continuously replaced; this occurs by a combination of diet and endogenous synthesis. Vegetarians obtain almost no dietary creatine. Creatine synthesis makes major demands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
224
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(231 citation statements)
references
References 94 publications
3
224
0
4
Order By: Relevance
“…Glycine may contribute to MPS and gains in body composition indirectly by supporting the synthesis and metabolism of creatine, which has been shown to improve lean body mass [37]. Creatine, along with phosphocreatine, plays a key role in cellular production and utilization of ATP [38], particularly in skeletal muscle. Because creatine is spontaneously converted to creatinine and excreted in urine, it must be continuously replaced by a combination of diet and endogenous synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycine may contribute to MPS and gains in body composition indirectly by supporting the synthesis and metabolism of creatine, which has been shown to improve lean body mass [37]. Creatine, along with phosphocreatine, plays a key role in cellular production and utilization of ATP [38], particularly in skeletal muscle. Because creatine is spontaneously converted to creatinine and excreted in urine, it must be continuously replaced by a combination of diet and endogenous synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Because creatine is spontaneously converted to creatinine and excreted in urine, it must be continuously replaced by a combination of diet and endogenous synthesis. Creatine synthesis requires the whole glycine molecule, the amidino group of arginine, and methylation typically provided by methionine [38]. Due to consumption of the entire glycine molecule in creatine synthesis it has been estimated that 16% of daily dietary glycine intake is required for creatine synthesis alone [38].…”
Section: Discussionmentioning
confidence: 99%
“…In the human gut, the anaerobic genus Clostridium were found to metabolize leucine to isocaproate and R-ketoisocaproate; 63 and creatine has also been shown to be co-metabolized in mammals and their gut microbiota. 64,65 Perturbed gut microbial changes observed in SCFAs, oligosaccharides and amino acids indicated vancomycin-induced changes in metabolism of these compounds, which may also explain the change in the relative amounts of R-ketoisocaproate and creatine in the urine.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide evidence that creatine supplementation during pregnancy may protect respiratory function in the neonate during the critical period immediately after birth. Although the many benefits of creatine therapy have been reviewed recently (40), its use in pregnancy has not been fully considered. This study also confirmed that dietary intervention during pregnancy provides a simple and effective means to prevent many of the deleterious effects arising from intrapartum hypoxia.…”
Section: Discussionmentioning
confidence: 99%